IMPLEMENTASI LAYANAN KONSELING KELOMPOK SEBAGAI UPAYA PENGUATAN KESEHATAN MENTAL WARGA BINAAN DI LAPAS KELAS III RANGKASBITUNG - Akbar Syafiq Nuzula; Arga Satrio Prabowo; Lenny Wahyuningsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mental health is an essential aspect of life, particularly for correctional inmates who face high psychological stress. This study aims to examine the effectiveness of a group counseling-based guidance and counseling program in reducing stress, anxiety, and depression among inmates at Class III Rangkasbitung Prison. The study employed a Community-Based Participatory Research (CBPR) approach, involving active collaboration between researchers, prison officers, and inmates. The sample consisted of 32 early adult inmates selected through purposive sampling, and psychological conditions were measured using the DASS-21 instrument. The program was implemented through several stages, including needs analysis, collaboration, program planning, delivery of classical guidance, group guidance, group counseling, individual counseling, and evaluation. The results indicated a significant increase in participants categorized as normal across all three psychological variables, alongside the reduction or elimination of moderate and severe categories after program implementation. These findings demonstrate that guidance and counseling services are effective in strengthening mental health, managing stress and anxiety, and reducing depression among inmates. The program highlights the importance of correctional institutions as rehabilitative spaces that integrate punitive and psychosocial development aspects and is recommended for sustainable implementation as a model for mental health intervention in correctional settings. Keywords: guidance and counseling, group counseling, stress, anxiety, depression, inmates, correctional institution.